Main-chain PPEGMEMA-b-PBTFVPP-b-PPEGMEMA perfluorocyclobutyl aryl ether-based amphiphilic ABA triblock copolymer: synthesis and self-assembly. Issue 94 (14th October 2015) - Feng, Chun; Yao, Wenqiang; Lu, Guolin; Li, Yongjun; Huang, Xiaoyu
<x xml:space="preserve">Abstract</x> A novel perfluorocyclobutyl aryl ether-based amphiphilic ABA triblock copolymers were synthesized via the site transformation strategy using sequential thermal [2π + 2π] step-growth cycloaddition polymerization and ATRP.